Not Just Participation: The Rise of the Eco‐Precariat in the Green Economy. Issue 2 (24th January 2020) - Neimark, Benjamin; Mahanty, Sango; Dressler, Wolfram; Hicks, Christina
Abstract: Despite recent attention to "frontier" green economies and the governance of emerging ecosystem services, the specific division of labour in these economies has been little studied. As many such initiatives are in the global South, labour's marginality potentially contributes to the existing precariousness of those who are more often identified as "participants". This article examines the roles and vulnerabilities of these actors: the carbon counters, species identifiers, GIS mappers, tree planters and others operating in the shadows. We draw on current understandings of labour and precarity to examine the geographical contours of an apparent and emerging "eco‐precariat": a socio‐economically diverse group of labourers that address the volatile demands of an ever‐expanding environmental service‐based economy. We illustrate our analysis drawing on examples from a Blue Carbon project in Kenya, ecosystem services project in the Philippines, and REDD+ scheme in Cambodia. We use these examples to theorise the nature of labour in these frontier economies and put forward a framework for analysing the eco‐precariat. We highlight the need to understand the precarity and marginalisation potentially created by this green division of labour in the provision of new ecosystem products and services. This framework contributes to ongoing analyses of labour as a central part of the green economy discourse and to larger discussions in the geographies of labour literature around the future of work in the global South and beyond.